Bilateral strength balance of knee extensor and flexor muscles in female soccer players - Andrades-Ramírez, O.; Ulloa-Díaz, D.; Romero-Vera, L.; Alfaro-Castillo, B.; Muñoz-Bustos, G.; Jorquera-Aguilera, C.; Carvajal-Parodi, C.; Chirosa-Ríos, L.-J. (Frontiers in Physiology, 2025)
Background: The aim of our study was analyze the bilateral strength balance of the knee extensor and flexor muscles in female soccer players.